Eficiência fotossintética e proteção oxidativa em mudas de cajueiro anão submetidas ao estresse salino - Silva, Anselmo Ferreira da (2016)
Abiotic stresses are responsible for the loss of agricultural production worldwide especially in semiarid regions, where prevailing adverse conditions such as high temperatures associated with drought, salinity and excessive solar radiation. These factors, singly or in combination, causes severe disturbances in the plant metabolism. Salinity, specifically, trigger severe reduction in photosynthetic capacity, which is associated with the induction of cellular oxidative damage. In this context, it was proposed to evaluate the efficiency of photosynthesis and oxidative protection, essential metabolic processes for plant productivity in dwarf cashew seedlings subjected to salt stress. The study was conducted with seedlings obtained from seeds, using two progenies of dwarf cashew (CCP 09 and CCP 76). Seedlings were subjected to salt stress with increasing doses of NaCl (0 to 100 mM) for 30 days. During this period, it were evaluated photosynthetic capacity, measures gas exchange and photochemical activity, and at the end of the trial (30 days of exposure to salt) was evaluated the oxidative protection, based on biochemical indicators of damage and protection. So, it is possible understood that both clones + accumulate Na in all plant parts, promoting a reduction in fresh weight. However, the CCP 09 + clone accumulated K gradually in leaves, favoring better growth of the aerial part and restricting the deleterious effects caused by salt. Salt stress drastically affected the photosynthetic apparatus, highlighting the clone CCP 09, pointing the PN variables, PN/CI and PN/E, with the exception of CI and E in relation to CCP 76. The salt stress promoted the increase of H2O2, only in clone CCP 09 while lipid peroxidation was dramatically reduced in both clones. Clones present specific responses antioxidants, in view of the higher enzyme activity (SOD and APX POX) to the CCP 76 and non-enzymatic (ASC and GSH), in addition to the POX activity to CCP 09. Based on the results, it is suggested that the best performance of the relationship shoot/root in + the clone CCP 09 was caused by the protective effect of K in leaves and relevant non-enzymatic antioxidative protection promoted by ASC and GSH, besides the enzyme activity of POX. This protection was evidenced in clone CCP 09 due to this being more efficient in carbon assimilation and use of tissue water than CCP 76.